Dukungan Sosial dengan Kecemasan Pasien Stroke di Rumah Sakit Stroke Nasional Bukittinggi - Febria Syafyu Sari (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2019)
Stroke can affect the whole body such as paralysis, cognitive deficits, speech difficulties, emotional difficulties, pain, and problems in daily life. The recovery process in post-stroke patients take a long time and also require social support because they are not able to solve their own problems. Data WHO (2012) show every years as many 17 million cause of death in the world because of stroke. Anxiety is a feeling of fear that is not clear and is not supported by the situation. When we feel anxious, the individual feels uncomfortable, afraid or may have a bad feeling. Social support for the sufferers urgently needed as long as the sufferers still able to understand the meaning of that support as an advocate for live.This study aimed to determine the social support relation with anxienty stroke patient. This research is a Cross-Sectional with Accidental Sampling method. This research do at National Stroke Hospital Bukittinggi with 160 respondens. The statistical test used is Chi-Square. The result of statistical test showed a significant between the social support relation with anxiety stroke patient with p-value = 0,000 (α ≤ 0,05).The hospital is expected to urge the family to more actively in volve in caring for stroke patients and provide counseling to them in order to better understand the importance of any rehabilitation program recommended.